Analysis of Industry Sector Growth Impact on Labor Absorption in Indonesia (2013-2021) - Pratnyaloka, Madhen Wiyan; Khusaini, Moh. (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The industrial sector plays an important role in Indonesia's economy. According to BPS data (2023), the contribution of the industrial sector to GDP is greater than that of the agricultural sector, highlighting its role in economic growth and job creation. This study analyzes the factors influencing labor absorption in Indonesia's industrial sector during the 2013-2021 period, focusing on variables such as output, capital, wages, and the number of firms. Secondary data from BPS is analyzed using a multiple regression model. The findings show that all variables have a significant influence, with output, capital, and wages having a positive effect, while labor absorption has a negative impact, which tends to decline due to increased automation and a shift towards capital-intensive industries that reduce the demand for manual labor. This study emphasizes the importance of policies that balance industrial modernization with labor market inclusivity.